Jugando las olas. El juego cinematográfico de Lars von Trier - Lencina, Victoria Julia (Imagofagia, 2021)
Traducción de los capítulos “Introduction” y "Chapter 1: Manifesto and Modernism", del libro Playing the waves. Lars von Trier's game cinema de Jan Simons. Amsterdam: Amsterdam University Press, 2007. Resumo: Tradução de “Introdução” e “Capítulo 1: Manifesto e Modernismo” de Jan Simons “Playing the waves. O jogo de cinema de Lars von Trier. Amesterdão: Amsterdam University Press, 2007. Abstract: Translation of “Introduction” and "Chapter 1: Manifesto and Modernism" of Jan Simons’ Playing the waves. Lars von Trier's game cinema. Amsterdam: Amsterdam University Press, 2007.